Multiple Criteria Stakeholder’s Roles in Ensuring the Sustainability of Gringsing Weaving - Ida Ayu Nyoman Saskara; Widhianthini Widhianthini; I Gusti Ayu Agung Virna Pryanka (Jurnal Ilmu Sosial dan Humaniora, 2024)
Bali is known to have the most types of wastra (traditional cloth) in Indonesia and is full of local wisdom values, one of which is Gringsing Weaving. This cloth is the only woven cloth in Indonesia that uses a double ikat weaving technique that takes a long time. The motifs and coloring are still traditional and use natural materials. Gringsing weaving has not only aesthetic value but also social and economic value. However, the departure of gringsing weaving is threatened due to the regeneration of craftsmen and competition with other relatively cheap fabric products. This research aims to analyze stakeholders' role in ensuring Tenun Gringsing's wishes, including convergence and divergence between actors. This research uses prospective analysis with MACTOR as tool analysis, where the data collection process is carried out through FGD. The respondents in the FGD are craftsmen, local figures, and the government. The identification results show that three internal and six external stakeholders are related and have an interest. Meanwhile, the objectives in context include economic, environmental, social, and cultural aspects. The results of the MACTOR analysis show that the most active actors in Gringsing Weaving tourism are traditional leaders. Tourists are stakeholders who have a value of disapproval of the goals of developing the human resources of craftsmen. Traditional leaders converge most with the Tenganan Village community and craftsmen related to Gringsing weaving. Traditional leaders have substantial differences with tourists. This further emphasizes the importance of the role of traditional leaders. This research contributes to the stakeholder scenario regarding the sustainability of Gringsing Weaving.